Should I Stay Or Should I Go? The importance of electricity rate design for household defection from the power grid. (15th March 2020) - Gorman, Will; Jarvis, Stephen; Callaway, Duncan
Highlights: 1.1% of United States households could find it privately economic to grid defect. Low load customers will find it easiest to defect from the grid. Defection up to 7% is possible if customers accept slightly less reliable service. Limiting inefficient load defection via fixed charges could lead to grid defection. Abstract: The cost declines of solar and storage technologies have led to concerns about customers disconnecting from utility service and self-supplying electricity. Prior research addressing this issue focused on average electricity tariffs, solar profiles, and demand without considering detailed customer heterogeneity. This paper fills the gap by analyzing how electricity tariffs that shift cost recovery away from variable charges towards fixed charges influence a customer's decision to disconnect from utility service. A linear optimization model is developed to size an off-grid solar/storage system. Technology cost and reliability parameters of the optimization model are then adjusted to calculate a range of off-grid costs. Unique rate structure information for over 2000 utilities in the United States is then used to compare grid costs to off-grid costs. The results show limited ability for solar/storage systems to economically substitute for grid services. However, 1% of households might disconnect from utility service in a scenario that accounts for future off-grid costs and updated tariff designs. We find that 3% of households in the Southwest and California have private economics that favor defection in this scenario, rising to as much as 7% in Hawaii. Grid defection could increase from 1% to 7% of United States households in a slightly reduced reliability scenario. These results indicate that utilities and regulators seeking to limit rooftop solar adoption by lowering variable charges face a significant possibility that the corresponding increase in fixed charges could lead to inefficient grid defection.